Implementation of Spiritual -Based Cognitive Behavioral Therapy on Misbehavior among Student in Modern Muhammadiyah Boarding School Pleret - Ummi Zahratul Mufidah; Sutarman; Aisyah Mutiaramadhan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This research is motivated by the existence of moral degradation by some students at PPM MBS Pleret, so if not handled it can have a broad impact on others. The purpose of this study is to examine the implementation of Cognitive Behavioral Therapy (CBT) based on spiritual intelligence values on santri delinquency at PPM MBS Pleret, what delinquencies cause the use of Cognitive Behavioral Therapy (CBT) based on spiritual intelligence values at PPM MBS Pleret, and the benefits of implementing Cognitive Behavioral Therapy (CBT) based on spiritual intelligence values on santri delinquency at PPM MBS Pleret. This research uses a qualitative research method with an analytical descriptive approach. The data collection used observation, interview, and documentation techniques. This research data analysis technique goes through four stages, namely: data reduction, data presentation, data validity test and conclusion. This thesis research describes the implementation of Cognitive Behavioral Therapy based on spiritual intelligence values on santri delinquency at PPM MBS Pleret. The results of this study indicate that the implementation of Cognitive Behavioral Therapy based on spiritual intelligence values at PPM MBS Pleret in theory PPM MBS Pleret has implemented CBT therapy with patterns, namely: (1) creating a relationship between Ustadz-ustadzah BK and the students concerned, (2) identifying problems from bad thoughts and actions, making students aware of themselves and applying CBT based on spiritual intelligence values, actions by adjusting the policies of the cottage order book, and monitoring or controlling.